Catalisadores nanoparticulados de paládio a partir de metodologias bioinspiradas - Souto, Robson da Silva (2021)
The application of green approaches in the synthesis of nanoparticulate catalysts has allowed gains in high efficiency and stability, in addition to the economic and environmental cost-benefit. Magnetic nanocomposites based on metal oxides, used as support for transition metal nanoparticles represent an advance in terms of separation efficiency and recycling of new catalysts. In this work, extracts of the species Rhamnidium elaeocarpum Reissek (Rhamnaceae) collected in the local, are used as reducing and stabilizing agents in the synthesis of magnetite (Fe3O4) and palladium (Pd0 ) nanoparticles. The biosynthesized magnetite nanoparticles, with an average of 80 nm size, were used in the synthesis process of the Fe3O4@ZnO composite used as support. This support received the deposition of biosynthesized palladium nanoparticles, with an average of 21.9 nm size. The prepared catalyst Fe3O4@ZnO-Pd was characterized by FTIR, XPS, TEM, HTEM, EDS, and VSM analysis. Furthermore, for the efficiency and stability evaluation of catalyst was applied in liquid-phase hydrogenation reactions of cyclohexane and 4-nitrophenol (4-NF), used as models of alkene compounds and nitrocompounds, respectively. The tests were conducted under environmentally friendly conditions, under an atmosphere of molecular H2, as a green source of H atoms, and at a mild temperature (75 °C). As a result, conversion values >96% were obtained after the 30-minute interval for both compounds. In the study of catalyst recycling, averages up to >94% were obtained in up to 17 reuses for cyclohexene and 21 for 4-NF until partially deactivated of catalyst. Comparison of the material produced in this work with other palladium-based catalysts, under approximate reaction conditions, by calculations of Rotation Frequency (FR) and Total Rotation Number (NRT) was performed. The values observed for FR were 9,519 and 167 h-1 and NRT of 73,934 and 1659 for cyclohexene and 4-NF, respectively. Finally, due to the superparamagnetic property presented by the support core, the catalyst allowed an easy dispersion in the reaction medium and fast separation with Nd magnet use.